Scaling of adult regional body mass and body composition as a whole to height: Relevance to body shape and body mass index. Issue 3 (8th November 2014) - Schuna, John M.; Peterson, Courtney M.; Thomas, Diana M.; Heo, Moonseong; Hong, Sangmo; Choi, Woong; Heymsfield, Steven B.
ABSTRACT Objectives Adult body mass (MB) empirically scales as height (Ht) squared (MB ∝ Ht2), but does regional body mass and body composition as a whole also scale as Ht2? This question is relevant to a wide range of biological topics, including interpretation of body mass index (BMI). Methods Dual‐energy X‐ray absorptiometry (DXA) was used to quantify regional body mass [head (MH), trunk, arms, and legs] and whole‐body composition [fat, lean soft tissue (LST), and bone mineral content (BMC)] in non‐Hispanic (NH) white, NH black, Mexican American, and Korean adults participating in the National Health and Nutrition Examination Survey (NHANES; n = 17, 126) and Korean NHANES (n = 8, 942). Regression models were developed to establish Ht scaling powers for each measured component with adjustments for age and adiposity. Results Exploratory analyses revealed a consistent scaling pattern across men and women of the four population groups: regional mass powers, head (∼0.8–1) < arms and trunk (∼1.8–2.3) < legs (∼2.3–2.6); and body composition, LST (∼2.0–2.3) < BMC (∼2.1–2.4). Small sex and population differences in scaling powers were also observed. As body mass scaled uniformly across the eight sex and population groups as Ht∼2, tall and short subjects differed in body shape (e.g., MH/MB ∝ Ht−∼1) and composition. Conclusions Adult human body shape and relative composition are a function of body size as represented by stature, a finding that reveals a previously unrecognized phenotypic heterogeneity as defined by BMI. These observations provide new pathways for exploring mechanisms governing the interrelations between adult stature, body morphology, biomechanics, and metabolism. Am. J. Hum. Biol., 27:372–379, 2015. <related-article related-article-type="source" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">© 2014 Wiley Periodicals, Inc</related-article>.